2016
DOI: 10.1002/jmri.25566
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic multi-echo DCE- and DSC-MRI in rectal cancer: Low primary tumor Ktrans and ΔR2* peak are significantly associated with lymph node metastasis

Abstract: Purpose: To implement a dynamic contrast-based multi-echo MRI sequence in assessment of rectal cancer and evaluate associations between histopathologic data and the acquired dynamic contrast-enhanced (DCE) and dynamic susceptibility contrast (DSC) -MRI parameters. Materials and Methods: This pilot study reports results from 17 patients with resectable rectal cancer. Dynamic contrast-based multi-echo MRI (1.5T) was acquired using a three-dimensional multi-shot EPI sequence, yielding both DCE-and DSC-data follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…The K trans value represents the transfer rate from plasma to the EES, which has a mixed microcirculatory blood flow and permeability weighting [15, 28]. Although a mixed situation occurs most commonly, there is an overall trend of a dominating effect of flow in untreated tumours [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The K trans value represents the transfer rate from plasma to the EES, which has a mixed microcirculatory blood flow and permeability weighting [15, 28]. Although a mixed situation occurs most commonly, there is an overall trend of a dominating effect of flow in untreated tumours [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that primary rectal cancer blood flow measured by DCE-MRI was significantly lower in patients with metastatic nodes, which also represents an unfavourable prognosis [28]. However, regarding the investigation by Yu et al [26], lymphovascular invasion was correlated with higher K trans , k ep and v e values.…”
Section: Discussionmentioning
confidence: 99%
“…As for the DSC analysis, a linear relationship was assumed between the change in R 1 = 1/T 1 and CA concentration, and an average precontrast T 1 -value measured from six patients was used (1350 msec in tissue). 9 The extended Tofts (ET) model 18 was fitted to the data with the equation:…”
Section: Image Postprocessingmentioning
confidence: 99%
“…DSC‐MRI is a CA‐based method whereby the T 2 *‐ (susceptibility) effect, rather than the T 1 ‐effect of the CA, is utilized to measure perfusion‐related metrics. DSC‐MRI has mainly been used in the brain due to dominant T 2 *‐effects in regions with an intact blood–brain barrier, but has recently also shown utility in staging of rectal cancer . Specifically addressing brain tumors, Bisdas et al found good correlation between perfusion measured by DSC‐MRI and IVIM‐derived metrics but generally poorer correlation between DCE‐MRI‐derived metrics and IVIM.…”
mentioning
confidence: 99%
See 1 more Smart Citation